PENGARUH PENGELOLAAN MODAL KERJA, PERGERAKAN MODAL USAHA, STRUKTUR MODAL USAHA DAN VOLUME USAHA TERHADAP PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013 - Purnamasari, Ellisa Luky; Setyawanti, Dandang (KIAT BISNIS, 2015)
The aims of the research are to determine how much influence the management of working capital, venture capital movement, capital structure and volume of profitabilitas in property and real estate companies lifed on the BEI. The data used in this research is secondary data. The sample used in this research is property and real estate company listedon the BEI, with the research period of 2013 by 41 companies. The technique research samples using purposive sampling method. The data were tested using multiple regression analysis and hypothesis testing. The hypothesis testing using f test and t test with significant level of 5%. The hypothesis in this research consist of : (a) working capital management efforts have no significant effect on profitability (b) venture capital movement have a significant impact on profitability (c) venture capital structure have no significant effect on profitability (d) business volume has a significant impact on profitability. Keyword : Working capital management, venture capital movement, structure venture capital, venture volume, profitability.